METODE ABACA-BAJA SALAH SATU ALTERNATIF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA BAGI ANAK KESULITAN BELAJAR - Meta Gusrianti (Jurnal Penelitian Pendidikan Khusus, 2015)
ABSTRACT: This study begins with learning difficulties a child’s inability to read in SDN 18 Koto Luar, Padang. The purpose of this research is to improve the child's reading ability nouns using the abaca-baja method. Abaca-baja method is a method of teaching reading method that combines syllables and play with cute illustrations. This was an experimental research which was conducted in the form of Single Subject Research by using A-B-A design. The data gotten in this research was analyzed by using visual graphic analysis. The subject of the research was a difficulty learner student. The target behavior was the student’s ability to read nouns well. The variable was measured by using percentage technique. The result of within and inter-condition analysis indicated that the tendency of direction, stability, data track and the level changes improved positively. The percentage of the data overlapped in inter-condition analysis was 0% and 60%. The smaller the overlapping percentage, the better the influence exerted by the intervention. Thus, it was concluded that the use of Abaca-baja method was effective to improve the difficulty learner’s ability to read nouns. Therefore, in order to improve the difficulty learners’ ability to read nouns, it was suggested to the teachers to use Abaca-baja method.     Keyword: Membaca; Anak Kesulitan Belajar; Metode Abaca-Baja.